Differential responses to seasonal soccer training in U-15 and U-17 players: Body composition, strength, agility, and effect size analysis - Rick Stoop; Georgios Georgiadis; Iván González-García (Sport, Exercise, and Injury, 2026)
Background: Training programs during adolescence play a crucial role in optimizing body composition and physical performance in youth soccer players. However, differences in training adaptations between age groups, particularly in agility performance, remain insufficiently explored. Objectives: This study aimed to examine the effects of a seasonal soccer training program on body composition, strength, and agility in U-15 and U-17 soccer players. Methods: A pre–post experimental design was applied to 28 male youth soccer players (U-15: n = 15; U-17: n = 13) competing in a football league in the Netherlands. Participants completed a 16-week training program consisting of technical, conditioning, tactical, and mental components. Body composition (height, body mass, lean mass, fat mass), jump performance (SJ, CMJ, CMJmax), isokinetic strength (knee flexion and extension peak torque), and agility (Illinois Agility Test) were assessed before and after the intervention. Data were analyzed using repeated-measures analysis of variance (ANOVA) and effect sizes were calculated using Cohen’s d. Results: In the U-15 group, significant improvements were observed only in knee flexion (70.2 ± 15.8 vs. 95.4 ± 23.5 Nm, p = 0.006, d = 1.25) and extension peak torque (75.1 ± 20.4 vs. 96.8 ± 18.9 Nm, p = 0.012, d = 1.10). In contrast, U-17 players demonstrated significant increases in lean mass (50.2 ± 3.1% vs. 53.4 ± 2.3%, p = 0.021), reductions in fat mass (11.0 ± 2.9% vs. 8.7 ± 2.5%, p = 0.037), improvements in agility performance (16.2 ± 0.7 vs. 15.4 ± 0.65 s, p = 0.008, d = 1.18), and knee flexion peak torque (78.4 ± 26.5 vs. 118.3 ± 28.7 Nm, p = 0.003, d = 1.45), together with significant gains in jump performance (p < 0.05). Most significant changes in the U-17 group were accompanied by large effect sizes (d = 0.85–1.45). Conclusions: The training program elicited greater physiological and performance adaptations in U-17 compared to U-15 players. The greater adaptations observed in the U-17 group may be partially influenced by differences in biological maturation; however, maturity status was not directly assessed in the present study.